Benefits Derived from Social Group Membership by Poultry Farmers in Ondo State, Nigeria - Temidire, Olumoyegun Adewumi; Aina, Olumoyegun Bolanle (Jurnal AGRISEP, 2024)
Social Capital is fast taking a defining role as a necessity for successful and sustainable agricultural enterprise. The network of farmers in developing countries like Nigeria has been seen to determine greatly their resilience, ability to escape poverty, take risks and overcome vulnerabilities. Investigating the benefits derived and constraints encountered by poultry farmers in membership of social groups was the main thrust of this study. A two-stage sampling procedure was employed to select 120 poultry farmers in Ondo state. Questionnaire containing open and closed ended questions were used to elicit information from respondents. Data collected was analysed using frequency counts, percentages and mean. Results reveal that majority of sampled poultry farmers were between 40-59 years of age (53.3%), male (62.5%), married (73.3%), with some level of formal education (85.8%), poultry farming experience of 1-10 years (71.7%) and farm size of between 1-1000 birds (71.7%). Livelihood security (mean=1.19), accessing health services (mean=1.08), recreation (mean=1.07) and consultancy services (mean=1.03) were the top benefits of social group membership reported among respondents. Major constraints to social group membership identified by the respondents were low financial capacity (mean=1.13), poor group coordination (mean=1.22), lack of education (mean=1.08), leadership issues (mean= 0.98) and religious differences (mean=0.95). Institutional support to strengthen social group membership because of its advantages; by providing financial incentives and leadership capacity building for small scale poultry farmers is canvassed.